Higiene do sono - SILVA, Arthur Felipe Afonso da; SILVA, Bianca Costa da; SILVA, Daniela Regina Ribeiro Londer da; SANTANA, Myrella de Souza; FERREIRA, Nicole Vieira (194, 2025)
O estudo aborda a importância da higiene do sono como estratégia não farmacológica para a promoção da saúde e melhoria da qualidade de vida. Tem como objetivo analisar como práticas simples, como manter horários regulares, evitar o uso de dispositivos eletrônicos antes de dormir e garantir um ambiente adequado, contribuem para a prevenção de distúrbios do sono e para o equilíbrio físico e mental. Caracteriza-se como uma pesquisa descritiva e qualitativa, realizada por meio de revisão bibliográfica de artigos publicados entre 2019 e 2024 e aplicação de formulário ao público geral. Objetivo Geral: Analisar a importância da higiene do sono como estratégia não farmacológica para a promoção da saúde e melhoria da qualidade de vida.

The study addresses the importance of sleep hygiene as a non-pharmacological strategy for promoting health and improving quality of life. Its objective is to analyze how simple practices, such as maintaining regular sleep schedules, avoiding the use of electronic devices before bedtime, and ensuring an adequate environment, contribute to the prevention of sleep disorders and the maintenance of physical and mental balance. It is characterized as a descriptive and qualitative research, conducted through a bibliographic review of articles published between 2019 and 2024 and the application of a questionnaire to the general public. General Objective: To analyze the importance of sleep hygiene as a non-pharmacological strategy for promoting health and improving quality of life, identifying its main practices and the benefits related to the prevention of sleep disorders.

The study addresses the importance of sleep hygiene as a non-pharmacological strategy for promoting health and improving quality of life. Its objective is to analyze how simple practices, such as maintaining regular sleep schedules, avoiding the use of electronic devices before bedtime, and ensuring an adequate environment, contribute to the prevention of sleep disorders and the maintenance of physical and mental balance. It is characterized as a descriptive and qualitative research, conducted through a bibliographic review of articles published between 2019 and 2024 and the application of a questionnaire to the general public. General Objective: To analyze the importance of sleep hygiene as a non-pharmacological strategy for promoting health and improving quality of life, identifying its main practices and the benefits related to the prevention of sleep disorders.
Sleep hygiene
Keywords: Sono; Prevenção de doenças; Ambiente e Saúde